Incidence, prevalence and clinical outcome of anaemia in inflammatory bowel disease: a population‐based cohort study. Issue 6 (1st August 2018) - Eriksson, Carl; Henriksson, Ida; Brus, Ole; Zhulina, Yaroslava; Nyhlin, Nils; Tysk, Curt; Montgomery, Scott; Halfvarson, Jonas
Summary: Background: The incidence and short‐term outcome of anaemia in inflammatory bowel disease (IBD) are largely unknown. Aim: To determine the incidence, prevalence and clinical outcome of anaemia in terms of resolution of anaemia within 12 months. We also planned to assess risk factors for anaemia in IBD. Methods: A random sample of 342 patients was obtained from the population‐based IBD cohort of Örebro University Hospital, Sweden, consisting of 1405 patients diagnosed between 1963 and 2010. Haemoglobin measurements recorded from 1 January 2011 to 31 December 2013 were extracted from the Clinical Chemistry data system. Results: In Crohn's disease, the incidence rate of anaemia was 19.3 (95% CI: 15.4‐23.7) per 100 person‐years and the prevalence was 28.7% (CI: 22.0‐36.2), compared with 12.9 (CI: 9.8‐16.5) and 16.5% (CI: 11.2‐22.9) for ulcerative colitis. Crohn's disease was associated with an increased incidence (OR = 1.60; CI: 1.02‐2.51) and prevalence of anaemia (OR = 2.04; CI: 1.20‐3.46) compared to ulcerative colitis. Stricturing disease phenotype in Crohn's disease (HR = 2.59; CI: 1.00‐6.79) and extensive disease in ulcerative colitis (HR = 2.40; CI: 1.10‐5.36) were associated with an increased risk of anaemia. Despite a higher probability of receiving specific therapy within 3 months from the diagnosis of anaemia, Crohn's disease patients had a worse outcome in terms of resolution of anaemia within 12 months (56% vs 75%; P  = 0.03). Conclusions: Anaemia is a common manifestation of IBD even beyond the first years after the diagnosis of IBD. Crohn's disease is associated with both an increased risk and a worse outcome.